Chiari I malformation in children with transverse myelitis. (18th August 2018) - Vadivelu, Sathya; Vadivelu, Sudhakar; Mealy, Maureen; Patel, Smurti; Kosnik-Infinger, Libby; Becker, Daniel
ABSTRACT: Purpose: Transverse myelitis (TM) is an acute inflammatory spinal cord injury. Asymptomatic Chiari I malformation (CMI) management is highly controversial, particularly when associated with a spinal syrinx. Here, we assess the occurrence of CMI in the pediatric TM population and management outcomes. Methods: We performed a retrospective cohort study based on 61 consecutively identified pediatric TM cases over an –8-year period. We reviewed demographic characteristics, radiographic findings, presenting symptoms, and long-term outcomes. Results: Eight CMI cases were identified within the TM cohort; all presented with TM by 16 months of age and affecting the cervical spinal cord. In three cases, CMI developed 15 months to 6 years after the onset of TM. One in 10 children with TM had CMI. Conclusion: These findings demonstrate a high prevalence of CMI in patients with TM. Large prospective clinical studies are needed to further investigate the natural history and recovery strategies of CMI involved with neuroinflammatory disorders.